Case report: Metastatic melanoma masquerading as apical hypertrophic cardiomyopathy - Ashraf, Muddasir; Jahangir, Arshad; Jan, M. Fuad; Muthukumar, Lakshmi; Neitzel, Gary; Tajik, A. Jamil (Frontiers in Cardiovascular Medicine, 2022)
Background: Cardiac tumors are usually metastatic. Melanoma is the tumor with the highest rate of cardiac metastasis. Clinicians need to be aware of the metastatic involvement of the left ventricular apex as a differential diagnosis of apical hypertrophic cardiomyopathy. Case summary: A 74-year-old female presented for evaluation of fatigue. The initial electrocardiogram and echocardiogram showed features of apical hypertrophic cardiomyopathy. The patient reported a lesion on her right forearm that had been present for many years, leading to its biopsy, which showed melanoma. Further evaluation with a chest computed tomography (CT) scan showed left lung nodules and nodular thickening of the left ventricular apex. Positron emission tomography showed an increased update of fluorodeoxyglucose in the left lung nodule and left ventricular apex, suggestive of metastatic spread of the melanoma. A CT-guided biopsy of the left lung nodule revealed melanoma. The patient was treated with ipilimumab initially, followed by paclitaxel with poor response to treatment, and later passed under hospice care. Conclusion: Metastatic tumor involving the left ventricular apex should always be considered in the differential diagnosis of apical hypertrophic cardiomyopathy, especially in patients with a history of melanoma, and advanced cardiac imaging, including cardiac magnetic resonance imaging, CT, and/or PET may help with narrowing down the differential diagnosis.